2016
DOI: 10.1017/s0031182016000111
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides infection in rodents: immune response and immune regulation

Abstract: The human pathogenic nematode Strongyloides stercoralis infects approximately 30-100 million people worldwide. Analysis of the adaptive immune response to S. stercoralis beyond descriptive studies is challenging, as no murine model for the complete infection cycle is available. However, the combined employment of different models each capable of modelling some features of S. stercoralis life cycle and pathology has advanced our understanding of the immunological mechanisms involved in host defence. Here we rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 141 publications
(252 reference statements)
1
49
0
1
Order By: Relevance
“…Here we confirm that experimental murine and natural human infections by threadworms are predominantly associated with Th2 responses (Chiuso-Minicucci et al, 2010; Anuradha et al, 2015; Breloer and Abraham, 2016). Mice infected with S. ratti displayed locally and systemically increased frequencies of Th2 cells and only low signs of intestinal immunopathology, which is in line with the mostly asymptomatic course of threadworm infections in human patients (Siddiqui and Berk, 2001; Vadlamudi et al, 2006; Montes et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Here we confirm that experimental murine and natural human infections by threadworms are predominantly associated with Th2 responses (Chiuso-Minicucci et al, 2010; Anuradha et al, 2015; Breloer and Abraham, 2016). Mice infected with S. ratti displayed locally and systemically increased frequencies of Th2 cells and only low signs of intestinal immunopathology, which is in line with the mostly asymptomatic course of threadworm infections in human patients (Siddiqui and Berk, 2001; Vadlamudi et al, 2006; Montes et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…We found that T and B cell-deficient Rag2 -/-mice exhibited a 20-day delay (i.e., requiring 32 days in total) in cessation of S. venezuelensis egg excretion during primary infections and a 25-day delay (i.e., requiring 37 days in total) in the secondary infection (versus no eggs detected during secondary infections in any of the wild-type mice) (Fig. 3A), underscoring the importance of an adaptive immune response for effective secondary immune responses to this nematode (8,11,13,14,41,(46)(47)(48). In addition, we confirmed that the number of adult worms in the intestines on day 8 of the primary infection was significantly higher in the Rag2 -/-mice than in the corresponding wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…We also examined whether MCs and/or basophils contribute to cessation of S. venezuelensis egg excretion during secondary infections. Several studies indicated that, in secondary nematode infections of wild-type mice, the larvae can be trapped in the skin and lungs before reaching the intestines, as reported for S. venezuelensis (39)(40)(41), Strongyloides ratti (41), and Nippostrongylus brasiliensis (42)(43)(44). In this study, we assessed fecal egg numbers as an indicator of whether larvae could reach the intestines and then produce eggs.…”
Section: Resultsmentioning
confidence: 93%
“…The interaction of Strongyloides with its host immune response is key to understanding the harm that it can cause to hosts, and the immunobiology of Strongyloides is reviewed here by Minka Breloer and David Abraham (Breloer and Abraham, 2016). In common with other helminths a Th2 response dominates host anti- Strongyloides responses.…”
mentioning
confidence: 99%
“…But, this results in different, site-specific effects acting against either migrating larvae within the host tissues or against parasitic adults in the host gut. The effectors acting against parasitic adults are mast cells [activated by the cytokines interleukin (IL)-3 and IL-9] and anti- Strongyloides immunoglobulin E (IgE) and IgG responses (Breloer and Abraham, 2016). The developmental choices of the Strongyloides life cycle are in part controlled by the host immune response (Viney and Kikuchi, 2016), and understanding what aspects of the host immune response Strongyloides sense, and how they sense it, to make these life cycle decisions is unknown, and something that deserves to be investigated.…”
mentioning
confidence: 99%